BEHAVIORAL PUBLIC ADMINISTRATION: NUDGING FOR BETTER COMPLIANCE IN TAX AND REGULATORY SYSTEMS - Asma, Wiszda; Witriana, Laili (Penelitian dan Pengembangan Ilmu, 2025)
Compliance with tax and regulatory systems is essential for effective governance, yet traditional sanction-based approaches remain costly and often ineffective. As a more adaptive alternative, behavioral public administration particularly through nudging strategies—has gained traction to promote voluntary compliance. However, the effectiveness of nudges varies across contexts, and comprehensive cross-national reviews remain limited. This study employs a narrative literature review of publications from 2008–2025 using Scopus and Web of Science, focusing on behavioral interventions in tax and regulatory settings. Using MINDSPACE and EAST frameworks, the study classifies nudge types and synthesizes their effectiveness. Findings indicate that social norm and salience-based nudges significantly enhance compliance, though outcomes are shaped by contextual moderators such as public trust, digitalization, and bureaucratic capacity. This review advances theoretical integration between behavioral economics and public administration and offers practical guidance for designing context-sensitive, evidence-based compliance policies.